2020
DOI: 10.1021/acsomega.0c00661
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput and Sensitive Analysis of Free and Total 8-Isoprostane in Urine with Isotope-Dilution Liquid Chromatography-Tandem Mass Spectrometry

Abstract: Oxidative stress (OS) plays a major role in the pathogenesis of various diseases in humans. OS is a result of an imbalance between reactive oxygen species (ROS) and the biologically available antioxidants that prevent or repair damage that ROS inflict on the host cells. ROS are naturally generated during normal mitochondrial respiration and by oxidative burst during the immune response. Many factors may influence OS, including genetics, diet, exercise, and exposure to environmental toxicants (e.g., tobacco smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Consequently, the use of natural products as food additives is favored. Regardless of the source for the bioactives, a fast, simple, and sensitive analytical method is required for their identification and quantification [ 11 , 12 ]. Traditionally, gas chromatography (GC) with flame ionization detector (FID) [ 13 , 14 , 15 , 16 , 17 ] or mass spectrometry (MS) [ 18 , 19 , 20 , 21 ] has been utilized for the determination phytosterols and tocopherols.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the use of natural products as food additives is favored. Regardless of the source for the bioactives, a fast, simple, and sensitive analytical method is required for their identification and quantification [ 11 , 12 ]. Traditionally, gas chromatography (GC) with flame ionization detector (FID) [ 13 , 14 , 15 , 16 , 17 ] or mass spectrometry (MS) [ 18 , 19 , 20 , 21 ] has been utilized for the determination phytosterols and tocopherols.…”
Section: Introductionmentioning
confidence: 99%
“… Ryu et al (2016) also reported a 20-fold increase in 8-iso-PGF2α level in wastewater after enzyme hydrolysis. The glucuronide conjugated forms of 8-isoprostane in human urine samples can vary between 30 to 80% of the total iso-prostane ( Holder et al, 2020 ; Yan et al, 2010 ). However, 2,3-dinor-iPF2α-III was not detected even after enzyme hydrolysis.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous assay of 8-isoprostane in urine resulted in recoveries ranging from 92.7 to 106.7% with a mean recovery of 99.7%, indicating that the results from our BAL fluid assay are consistent from analysis of a different physiological matrix. ( Holder et al, 2020 ) We compared the ISTD responses between unextracted calibration samples and extracted samples to evaluate sample recovery and calculated an average recovery of 55% for all extracted samples.…”
Section: Resultsmentioning
confidence: 99%
“…The LC-MS/MS instrument parameters were kept the same as our previously published CLIA urinary assay. ( Holder et al, 2020 ) In brief, chromatographic separation was achieved using a Waters ACQUITY reversed-phase column (150 mm × 2.1 mm, particle size 1.8 μm, C18) and a Waters ACQUITY reversed-phase pre-column (5 mm × 1 mm, particle size 1.7 μm, C18) (Milford, MA, United States) on an ultra high performance liquid chromatographic system from Shimadzu Corp. (Columbia, MD, United States) A gradient program was performed with a combination of 0.15% formic acid in water (mobile phase A) and acetonitrile in 0.15% formic acid in water (v/v 1:1) (mobile phase B). The combined chromatographic flow rate was 0.65 ml/min, and acetonitrile was infused, post-column, at 0.15 ml/min.…”
Section: Methodsmentioning
confidence: 99%